Problems of empowerment in linguistic research - Cameron, Deborah (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
The unequal social positioning of researcher and researched is an enduring feature of normal social science. People who are regarded as a ‘social problem’ (the poor, excluded, criminalized, ‘minorities’, etc.) inevitably also become a social science research problem; even if there is no explicit agenda of social control, the knowledge we make about such people contributes to the workings of disciplinary power. Yet when you are actually doing research in the ‘field’, you rarely feel that your informants are powerless, or that you yourself are powerful. On the contrary, you may feel the opposite is true. It was this sort of complexity we wanted to explore under the heading of language and subjectivity.